Vitamin B12 Enhances Nerve Repair and Improves Functional Recovery After Traumatic Brain Injury by Inhibiting ER Stress-Induced Neuron Injury - Wu, Fangfang; Xu, Ke; Liu, Lei; Zhang, Kairui; Xia, Leilei; Zhang, Man; Teng, Chenhuai; Tong, Heyan; He, Yifang; Xue, Yujie; Zhang, Hongyu; Chen, Daqing; et al. (Frontiers in Pharmacology, 2019)
Traumatic brain injury ( TBI ) is one of the most common causes of neurological damage in young populations.VitaminB12, which can promote neuronal cell axonal growth and the recovery process following peripheral nerve damage, is currently used for the clinical treatment of peripheral nerve damage, but its effectiveness in TBI repair is still not clear. In this study, we hypothesized that vitaminB12 administration attenuates TBI, specifically by enhancing axon regeneration, and improves functional recovery. The biological function of vitaminB12 was characterized using haematoxylin and eosin ( H&E ) staining, Luxol fast blue staining, western blotting, and immunostaining. The results showed that vitaminB12 improved the recovery of neurological function after TBI in mice, which may be related to its inhibition of endoplasmic reticulum stress and the apoptosis signalling pathway. Furthermore, vitamin B12 induced microtubule stabilization, remyelination and myelin reparation, while 4-phenylbutyric acid ( 4-PBA ) ( an endoplasmic reticulum stress inhibitor ) had the same effects. Our results suggest that vitamin B12 may be useful as a novel neuroprotective drug for TBI.